Influence of preeclampsia/eclampsia on Peruvian women and their newborns, 2000-2006 - Romero, José Pacheco (2015)
Objectives: To determine preeclampsia (PE) and eclampsia (E) maternal characteristics in Peruvian hospitals and influence on mother and neonate. Design: Observational, analytical, cross-sectional type study. Setting: Hospitals of the Ministry of Health of Peru. Participants: Pregnant women with or without preeclampsia and eclampsia (PE/E) and their newborns. Methods: Perinatal Information System SIP 2000 data of 310 795 pregnant women and their 314 078 newborns attended at 28 MINSA hospitals during 2000-2006 were analyzed. Data analysis was done using SPSS 14.0 and Epi Info 6.0 statistical packages. Main outcome measures: Maternal and neonatal characteristics and influence of PE/E. Results: From all pregnant women 295 075 did not have PE/E (94.9%) and 15 720 had PE/E (5.1%) [preeclampsia 14 993 (4.8%) and eclampsia 727 (0.24%)]. Significant preeclampsia-associated factors were maternal age 35 or over, multiple pregnancy, abruptio placentae, and abdominal delivery; factors associated to eclampsia were age less than 20, single state, illiteracy/low level of education, multiple pregnancy abruptio placentae, and cesarean section. Significant findings in newborns of PE/E mothers were low birthweight for gestational age, low Apgar score needing resuscitation, and newborn weight less than 2 500 at discharge. More maternal and neonatal deaths occurred in eclampsia in relation to pregnant women without PE/E or with non-convulsive preeclampsia. Conclusions: In this study of MINSA Peruvian hospitals preeclampsia incidence and maternal and neonatal morbidity and mortality were similar to findings in the literature, and were related to social and age factors. It is necessary to continue determining evolution of this fearsome complication of pregnancy in Peru. Keywords: Preeclampsia, eclampsia, Peruvian pregnant women, maternal mortality, neonatal mortality.